ISLAM DAN TOLERANSI - Dwi Anriyani; St. Nurmala Binti Rusding; Abbas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Tolerance in Islam is a fundamental principle that underpins social interactions in a diverse society. This article aims to investigate the understanding and practice of tolerance within Islam using a qualitative approach. The methodology includes in-depth interviews with various respondents, including religious leaders, academics, and community members, providing a broad perspective on tolerance. The research design is a case study focused on thematic analysis to identify the thought patterns and experiences of respondents regarding tolerance. The findings indicate that tolerance in Islam is perceived as an attitude of mutual respect and acceptance of differences. Respondents emphasize the importance of interfaith dialogue and collaboration in social activities to foster harmonious relationships. Although many have implemented the values of tolerance in their daily lives, challenges such as extremism and the misuse of religious teachings remain obstacles. The discussion in this article highlights that inclusive religious education and open dialogue are essential to address these challenges. By referencing the teachings of the Quran, which stresses that there is no compulsion in religion, this article concludes that strengthening the values of tolerance in the Muslim community is crucial for creating a peaceful and harmonious environment. It is hoped that these findings can serve as a reference to enhance awareness of the importance of tolerance in religious life and encourage efforts toward a more inclusive society.